2018
DOI: 10.1016/j.actbio.2018.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Predicting and understanding collagen remodeling in human native heart valves during early development

Abstract: The hemodynamic functionality of heart valves strongly depends on the distribution of collagen fibers, which are their main load-bearing constituents. It is known that collagen networks remodel in response to mechanical stimuli. Yet, the complex interplay between external load and collagen remodeling is poorly understood. In this study, we adopted a computational approach to simulate collagen remodeling occurring in native fetal and pediatric heart valves. The computational model accounted for several biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…A previous study also showed the decrease of peak stress from 1.42 MPa in the isotropic bovine pericardium valve model to 1.13 MPa in the anisotropic model through computational modeling [60]. Therefore, anisotropic PEGDA-ASF leaflets with layered fibrous structures can mimic the circumferential alignment of collagen fibers in native heart valves, as well as their response to mechanical stimuli [61], and attenuate the stress concentration under closing pressure gradient, which may improve the durability of the PHV prosthesis.…”
Section: Discussionmentioning
confidence: 81%
“…A previous study also showed the decrease of peak stress from 1.42 MPa in the isotropic bovine pericardium valve model to 1.13 MPa in the anisotropic model through computational modeling [60]. Therefore, anisotropic PEGDA-ASF leaflets with layered fibrous structures can mimic the circumferential alignment of collagen fibers in native heart valves, as well as their response to mechanical stimuli [61], and attenuate the stress concentration under closing pressure gradient, which may improve the durability of the PHV prosthesis.…”
Section: Discussionmentioning
confidence: 81%
“…Early phenomenological models hypothesized that collagen fibers align along or in between the directions of principal stress or strain, which enabled them to successfully predict the collagen organization in heart valves and arteries (Driessen et al 2003(Driessen et al , 2004(Driessen et al , 2005(Driessen et al , 2008Boerboom et al 2003;Baek et al 2006;Kuhl et al 2007;Hariton et al 2007). In more recent studies, models of collagen remodeling have been developed that accounted for the effects of cell behavior, such as contractility and cell alignment, to unravel the underlying biological mechanisms (Loerakker et al 2014(Loerakker et al , 2016Soares et al 2014;Ristori et al 2018a). These models suggest that collagen remodeling is driven by mechanical stimuli both directly, via the influence of strain, and indirectly, via mechanomediated cell behavior.…”
Section: Collagen Remodeling Modelsmentioning
confidence: 99%
“…Additionally, it has been predicted that mechanical stimuli provided by hemodynamic loading dominate the cell-mediated collagen remodeling process in TEHVs implanted in the aortic position, whereas the influence of contractility was predicted to be more important for TEHVs implanted in the pulmonary position (Loerakker et al 2016). To simulate long-term collagen remodeling in heart valves, the influence of topographical stimuli was included in a more recent study as well (Ristori et al 2018a(Ristori et al , 2018b. Simulations with this model revealed that cell traction and reorientation in response to mechanical stimuli can potentially explain the emergence of an anisotropic collagen organization in fetal heart valves, while the coalignment of collagen fibers with cells seems vital for maintaining and reinforcing the adopted collagen organization over time (Ristori et al 2018a).…”
Section: Collagen Remodeling Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormalities in the cardiovascular system are found to be common in OI patients, including valvular disease, atrial fibrillation and heart failure, and the more severe the OI phenotype, the higher the risk of cardiovascular abnormalities ( 9 , 10 ). As valves, tendinous cords, fibrous rings, and the cardiac septum of hearts are mainly composed of type I and III collagen, type I collagen contributes to the stiffer and rigid property of the myocardium ( 11 ). Therefore, a decrease of the collagen was associated with a more compliant ventricle, which results in increased LV diastolic internal diameters and volume ( 12 ).…”
Section: Introductionmentioning
confidence: 99%